Effects of biochar on dechlorination of hexachlorobenzene and the bacterial community in paddy soil. (November 2017) - Song, Yang; Bian, Yongrong; Wang, Fang; Herzberger, Anna; Yang, Xinglun; Gu, Chenggang; Jiang, Xin
Abstract: Anaerobic reductive dechlorination is an important degradation pathway for chlorinated organic contaminants in paddy soil. This study investigated the effects of amending paddy soil with wheat straw biochar on both the dechlorination of hexachlorobenzene (HCB), a typical highly chlorinated contaminant, and on the structure of soil bacteria communities. Soil amendment of 0.1% biochar did not significantly affect the dechlorination of HCB in the soil. However, biochar amendment at higher application levels (5%) stimulated the dechlorination of HCB in the first month of anaerobic incubation and inhibited the dechlorination of HCB after that period. The stimulation effect may be ascribed to the graphite carbon and carbon-centered persistent radicals, which are redox active, in biochar. The inhibiting effect could be partly ascribed to the reduced bioavailability of HCB in biochar-amended soils. High-throughput sequencing revealed that the amendment of biochar changed the soil bacterial community structure but not the bacterial abundances and diversities. The relative abundance of Dehalococcoidaceae in the tested soils showed a significant relationship with the dechlorination percentages of HCB, indicating that Dehalococcoidaceae may be the main HCB-dechlorinating bacteria in the studied paddy soil. The results indicated that low application levels of biochar did not affect the dechlorination of HCB in the paddy soil, while high application levels of biochar mainly inhibited the dechlorination of HCB due to the reduced bioavailability of HCB and the reduced abundances of certain dechlorinating bacteria in the biochar-amended paddy soil. Graphical abstract: Highlights: HCB dechlorination in biochar-amended paddy soil was investigated. Biochar initially stimulated the HCB dechlorination due to its redox activity. The bioavailability of HCB in biochar-amended soil decreased. The dissipation of HCB was correlated with the abundance of Dehalococcoidaceae. Biochar did not significantly affect the bacterial community diversity in the soil.